Some integral inequalities for harmonic h-convex functions involving hypergeometric functions - Mihai, Marcela V.; Noor, Muhammad Aslam; Noor, Khalida Inayat; Awan, Muhammad Uzair (Applied mathematics and computation, 2015)
The aim of this paper is to establish some new Hermite–Hadamard type inequalities for harmonic h-convex functions involving hypergeometric functions. We also discuss some new and known special cases, which can be deduced from our results. The ideas and techniques of this paper may inspire further research in this field.